Are there positive effects of having a sibling with special needs? Empathy and prosociality of twins of children with non‐typical development. Issue 4 (23rd February 2022) - Rum, Yonat; Genzer, Shir; Markovitch, Noam; Jenkins, Jennifer; Perry, Anat; Knafo‐Noam, Ariel
Abstract: This study examined whether typically developing (TD) twins of non‐TD children demonstrate enhanced empathy and prosociality. Of 778 Hebrew‐speaking Israeli families who participated in a twin study, 63 were identified to have a non‐TD child with a TD twin, and 404 as having both twins TD. TD twins of non‐TD children (27% males) were compared to the rest of the cohort of TD children (46% males) on measures of empathy and prosociality. Participants were 11 years old. TD twins of non‐TD children scored significantly higher than TD twins of TD children in a measure of cognitive empathy ( d  = .43). No differences were found in emotional empathy and prosociality. The specificity of the positive effect on cognitive empathy is discussed.